The Causal Effects of Lipid Profiles on Sleep Apnea - Tang, Hongyi; Zhou, Qing; Zheng, Fu; Wu, Tong; Tang, Yi-Da; Jiang, Jiuhui (Frontiers in Nutrition, 2022)
Introduction: observational studies have suggested that lipid profiles were associated with the risk of sleep apnea (SA). However, the specific lipid types and whether this relationship has a causal effect are uncertain. This study used two-sample Mendelian randomization (MR) and multivariable Mendelian randomization (MVMR) to investigate the potential causal relationship between lipid profiles and the risk of SA. Methods: We used the largest Genome-Wide Association Study (GWAS) of European participants from UK-Bank. After rigorous single nucleotide polymorphisms screening process to remove confounding effects, we performed MR and MVMR to explore the causal relationship between lipid profiles and SA risk. Results: Both MR and MVMR showed the causal effects of increased triglycerides on SA risk (MR: per 10 units Odds ratio (OR): 1.0156, 95% CI: 1.0057-1.0257, P Value=0.002; MVMR: per 10 units OR: 1.0229, 95% CI: 1.0051-1.0411, P Value=0.011). The sensitivity analysis including Cochran’s Q test, MR-Egger intercept and MR pleiotropy residual sum and outlier test (MR-PRESSO) indicated our findings were robust. The causal effects of triglyceride on sleep apnea did not change after adjusting for potential confounders (obesity, age, sex, airway obstruction). Conclusion: Genetically increased triglyceride levels have independent causal effects on the risk of sleep apnea without the confounding effects of obesity, suggesting that lowering triglyceride concentrations may help to reduce the risk of sleep apnea.